Ex Vivo Restimulation of Human PBMC Expands a CD3+CD4-CD8-γδ+ T Cell Population That Can Confound the Evaluation of CD4 and CD8 T Cell Responses to Vaccination - B. J. Sedgmen; L. Papalia; L. Wang; A. R. Dyson; H. A. McCallum; C. M. Simson; M. J. Pearse; E. Maraskovsky; D. Hung; P. P. Eomois; G. Hartel; M. J. Barnden; et al. (Clinical and Developmental Immunology)
The measurement of vaccine-induced humoral and CD4+ and CD8+ cellular immune responses represents an important correlate of vaccine efficacy. Accurate and reliable assays evaluating such responses are therefore critical during the clinical development phase of vaccines. T cells play a pivotal role both in coordinating the adaptive and innate immune responses and as effectors. During the assessment of cell-mediated immunity (CMI) in subjects participating in a large-scale influenza vaccine trial, we identified the expansion of an IFN-γ-producing CD3+CD4-CD8-γδ+ T cell population in the peripheral blood of 90/610 (15%) healthy subjects. The appearance of CD3+CD4-CD8-γδ+ T cells in the blood of subjects was transient and found to be independent of the study cohort, vaccine group, subject gender and ethnicity, and ex vivo restimulation conditions. Although the function of this population and relevance to vaccination are unclear, their inclusion in the total vaccine-specific T-cell response has the potential to confound data interpretation. It is thus recommended that when evaluating the induction of IFN-γ-producing CD4+ and CD8+ immune responses following vaccination, the CD3+CD4-CD8-γδ+ T cells are either excluded or separately enumerated from the overall frequency determination.